2023
DOI: 10.3390/cimb45040231
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Arginine Metabolism in Immunopathogenesis of a Wide Range of Diseases: Is There a Way to Pass between Scylla and Charybdis?

Abstract: More than a century has passed since arginine was discovered, but the metabolism of the amino acid never ceases to amaze researchers. Being a conditionally essential amino acid, arginine performs many important homeostatic functions in the body; it is involved in the regulation of the cardiovascular system and regeneration processes. In recent years, more and more facts have been accumulating that demonstrate a close relationship between arginine metabolic pathways and immune responses. This opens new opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 241 publications
0
4
0
Order By: Relevance
“…One of the most evolutionarily ancient strategies used by microbes to interfere with immune response and immune evasion is based on nutrient depletion in the microenvironment of host cells [21,50]. Here, we investigated an effect of bacterial arginine-hydrolyzing enzyme, ADI, on human peripheral blood T cell activation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most evolutionarily ancient strategies used by microbes to interfere with immune response and immune evasion is based on nutrient depletion in the microenvironment of host cells [21,50]. Here, we investigated an effect of bacterial arginine-hydrolyzing enzyme, ADI, on human peripheral blood T cell activation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, even such a local arginine decrease can be sufficient to suppress immune cell functions. Pathogenic microbes expressing ADI may create metabolic background, resulting in alteration of immune reaction, nonproductive inflammation, and elevated risk of reinfection [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first case of pneumonia of unknown cause was reported in December 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread rapidly worldwide, posing a significant threat to human health. Severe COVID-19 might also be accompanied by various complications, such as pneumonia, acute respiratory distress syndrome, and sepsis [15], which might be related to the immune dysfunction and cytokine storm caused by COVID-19 [16,17]. Simultaneously, many studies reported that many patients infected with the SARS-CoV-2 also have gastrointestinal symptoms, which include anorexia, nausea, vomiting, diarrhea, and abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the L-Arg metabolic pathways in specific pathological conditions is essential to treating the pathology. Therefore, discovering a therapy that regulates the metabolism of L-Arg remains difficult [17].…”
mentioning
confidence: 99%